Most valuable player of the UAAP season - Allado, Don (Animo Repository, 1998)
DLSU Basketball team member Don Allado was awarded the Most Valuable Player of the UAAP season. Two other Archers, Dino Aldeguer and Ren-Ren Ritualo, made it to the mythical five.